PENGEMBANGAN PRODUKSI DAN PEMASARAN MADU WETAR - Mersiana Sahureka; Troice Siahaya; Wilma N Imlabla (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
The purpose of this research is marketing of wetar honey in order to know the marketing chain of wetar honey and the factors that influence the production and marketing of wetar honey.The research method used is a qualitative description method and data collection were conducted through interviews and FGDs with farmers group of wetar honey and also conducted laboratory test of wetar honey sample at Ambon Food and Drug Administration (BPOM) to obtain certificate. The results of this research are quantitatively and qualitatively describe. The results achieved in this study wetar honey business provides a very large result for the improvement of the community economy if there is a development effort both in terms of production ie from honeycomb to packaging, as well as marketing terms which are marketing, distribution dan promosion developed.. Total respondent increase income from the development of wetar honey is Rp 50.000 – Rp 70.000 / 500 ml. Based on the letter from BPOM Ambon Number PM.02.04.1092.04 to the honey parameter test for 500ml size has passed the test / eligible for consumption.